Narcolepsy: A case with polysomnographic findings - Yasmin, Fatema; Hassan, Mohammad Rashidul; Khanam, Rawshan Arra (Bangladesh Critical Care Journal, 2022)
Narcolepsy is a sleep disorder presented with excessive sleepiness. Excessive sleepiness is key symptom of Narcolepsy. In obstructive sleep apnea excessive daytime sleepiness is also a remarkable symptom. Here we presented a 67-year-old female with uncontrollable sleep attacks and hypnagogic hallucination. She was previously diagnosed as obstructive sleep apnea and under BiPAP therapy for last few years. Her multiple sleep latency test become positive to meet diagnostic criteria for Narcolepsy. Clinicians should be cautious about possibilities of coexisting sleep disorders like Narcolepsy and obstructive sleep apnea in excessive day time sleepiness complaining patients. Bangladesh Crit Care J September 2022; 10(2): 161-162